2005
DOI: 10.1093/ndt/gfi304
|View full text |Cite
|
Sign up to set email alerts
|

The safety of gadolinium in patients with stage 3 and 4 renal failure

Abstract: An ARF can occur after gadolinium-based contrast agents in patients with moderate to severe chronic renal failure. Risk factors for ARF after gadolinium toxicity include diabetic nephropathy and low GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 16 publications
0
74
0
3
Order By: Relevance
“…In contrast to the previous reports, a number of studies (27)(28)(29)(30)(31) suggested that GBC agents exhibit variable degrees of nephrotoxicity (Table 3). A retrospective study examined the effect of gadopentetate on kidney function in 260 patients, 195 of whom had underlying CKD (27).…”
Section: Presence Of Nephrotoxicity With Gbc Agentsmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast to the previous reports, a number of studies (27)(28)(29)(30)(31) suggested that GBC agents exhibit variable degrees of nephrotoxicity (Table 3). A retrospective study examined the effect of gadopentetate on kidney function in 260 patients, 195 of whom had underlying CKD (27).…”
Section: Presence Of Nephrotoxicity With Gbc Agentsmentioning
confidence: 68%
“…A retrospective study examined 91 patients with stages 3 and 4 CKD for contrast nephrotoxicity (increase in serum creatinine of 0.5 mg/dl within 24 to 72 h) (29). The patients received one of three different GBC preparations (0.2 mmol/kg).…”
Section: Presence Of Nephrotoxicity With Gbc Agentsmentioning
confidence: 99%
“…Recent reports have suggested that gadolinium-based contrast agents may lead to acute renal failure in patients with advanced renal disease (22,23). We also routinely obtain images through the abdomen with steady-state free-precession gradient echo and fat-saturated T2-weighted spin echo sequences before gadolinium administration.…”
Section: Study Limitationsmentioning
confidence: 99%
“…This is because there are wide variations in definitions of AKI from one study to another (Table 4). AKI has been defined as an increase in sCre >0.3 mg/dL, 12 >0.5 mg/dL, 5,8,13 and >1 mg/dL. 14 Additionally, outcome data based on comorbidities before MRI examinations were not reported in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although it was thought to be safe and nonnephrotoxic at the approved doses for MRI and magnetic resonance angiography (MRA) examinations (≤0.3 mmol/kg), 4 Gd-CM has recently been reported to induce a reversible decrease of the glomerular filtration rate (GFR) in a high-risk group, especially in patients with renal impairment. [5][6][7][8][9] Additionally, patients usually have varied preexisting comorbidities [such as coronary artery disease (CAD), hypertension (HTN), diabetes, sepsis] when undergoing MRI or MRA examinations. However, additional studies have not confirmed whether these comorbid conditions are risk factors for Gd-induced nephropathy at low doses of Gd-CM.…”
Section: Introductionmentioning
confidence: 99%